2011
DOI: 10.5145/kjcm.2011.14.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Multilocus Sequence Typing of Vancomycin-ResistantEnterococcus faeciumIsolated from the Chungcheong Area

Abstract: Background: Enterococcus faecium has emerged as an important nosocomial pathogen worldwide, and this trend has been associated with the dissemination of a genetic lineage designated clonal complex 17 (CC17). In the present study, characterization of the glycopeptide resistance mechanism, genetic relatedness, and pathogenicity in isolates of vancomycin-resistant E. faecium in the Chungcheong area were investigated. Methods: A total of 37 consecutive, non-duplicate, vancomycin-resistant E. faecium were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(37 reference statements)
0
2
1
Order By: Relevance
“…Cho et al in Korea reported VRE ST 192, ST 78, ST 17, and ST 414 (highest to lowest frequency) in 2011 [22]. In our study, however, VRE ST 414 was the most frequent type.…”
Section: Resultscontrasting
confidence: 61%
“…Cho et al in Korea reported VRE ST 192, ST 78, ST 17, and ST 414 (highest to lowest frequency) in 2011 [22]. In our study, however, VRE ST 414 was the most frequent type.…”
Section: Resultscontrasting
confidence: 61%
“…CC17 was defined by using an MLST assay and is regarded as excellent example of cumulative evolutionary processes. In the majority of the E. faecium isolates, CC17 is characterized by ampicillin and quinolone resistance as well as the presence of a putative pathogenicity island, including the esp gene [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primers chosen for amplification are shown in table (1). Rapid DNA extraction method was performed, PCR amplification was done as described by Co et al 15 .…”
Section: Detection Of Vana and Vanb Genes In Vrementioning
confidence: 99%